ALGORITHM FOR OPTIMIZING ORGANIC CARBON AND NITROGEN FLOWS ON RECLAIMED LANDS - Mikhail N. Lytov (Мелиорация и гидротехника)
Purpose: to develop scientific approaches and an algorithm for optimizing organic carbon and nitrogen flows on reclaimed lands. Materials and methods. The working hypothesis of the research is that any level of agrocenosis bioproductivity requires a proportional amount of decomposable organic matter, which should not exceed a certain share of labile organic matter contained in the soil. Results. An algorithm that operates with two main regulators: the application mass of mineral nitrogen and organic matter, and determines the optimal balance for them, ensuring at least a non-negative trend in stable humus reproduction while achieving target indicators for the level of agrocenosis bioproductivity, has been developed. The algorithm is based on forecasting the dynamics of organic matter decomposition under given conditions. The dynamics of decomposition determines the amount of nitrogen released in the soil and the bioproductivity of crops correlated with it, on the one hand, and the direction of the transformation processes of pools of stable and labile organic matter, on the other hand. To solve the optimization problem on the part of the “carbon” branch of the algorithm, a limitation of the permissible decomposition of labile forms of organic matter is established. On the part of the “nitrogen” branch of the algorithm, the target function of achieving the planned agrocenosis bioproductivity is used. As a result of the solution, the main parameters of the application of mineral forms of nitrogen and organic matter are derived, including crop-root residues, straw biomass, green manure, livestock waste and products of their processing. Conclusion: an algorithm for optimizing the management of organic carbon and nitrogen flows is proposed, which allows solving problems of intensifying production, preserving and expanding the soil fertility reproduction on reclaimed lands.